X‐ray microtomography (micro‐CT): a reference technology for high‐resolution quantification of xylem embolism in trees. (18th July 2014) - COCHARD, H.; DELZON, S.; BADEL, E.
Abstract As current methods for measuring xylem embolism in trees are indirect and prone to artefacts, there is an ongoing controversy over the capacity of trees to resist or recover from embolism. The debate will not end until we get direct visualization of the vessel content. Here, we propose desktop X‐ray microtomography (micro‐CT) as a reference direct technique to quantify xylem embolism and thus validate more widespread measurements based upon either hydraulic or acoustic methods. We used desktop micro‐CT to measure embolism levels in dehydrated or centrifuged shoots of laurel – a long‐vesseled species thought to display daily cycles of embolism formation and refilling. Our direct observations demonstrate that this Mediterranean species is highly resistant to embolism and is not vulnerable to drought‐induced embolism in a normal range of xylem tensions. We therefore recommend that embolism studies in long‐vesseled species should be validated by direct methods such as micro‐CT to clear up any misunderstandings on their physiology.